International law - Klabbers, Jan (Cambridge University Press, 2013)
"Written by one of the world's leading international lawyers, this is a landmark publication in the teaching of international law. International law can be defined as 'the rules governing the legal relationship between nations and states', but reality is much more complex, with political, diplomatic and socio-economic factors shaping the law and its application. This refreshingly clear, concise textbook encourages students to view international law as a dynamic system of organizing the world. Bringing international law back to its first principles, the book is organized around four questions: where does it come from? to whom does it apply? how does it resolve conflict? what does it say? Building on these questions with both academic rigour and clarity of expression, Professor Klabbers breathes life and energy into the subject. Footnotes point students to the wider academic debate while chapter introductions and final remarks reinforce learning"--Provided by publisher.